The Visionaries of Laodicea - Goulder, Michael Douglas (Journal for the study of the New Testament, 1991)
Jewish Christians included visionaries. Such men—and women—were ravished out of the body to heaven and given access to the Throne, to praise God's glory, and even to be seated by it. They needed to be holy, both obeying Torah, and fasting and abstaining from sex. They passed through seven heavens guarded by formidable powers whose names they took on seals. Such powers filled the heavens, which were seen as a succession of temples; above all was God, pictured from Cant. 5 as having enormous size (cf. Shi'ur Qoma, the Measure of [God's] Stature). 'Ephesians' (a genuine Pauline letter, to the Laodicean church) was written to contest these claims. All Christians have access to God in Christ, who has ascended above all the heavens, seated with him by God with the powers under his feet, the Church being the temple he fills. It is the measure of the stature of Christ which matters, in love.